INVESTIGATING THE MOLECULAR MECHANISMS OF ATHEROSCLEROSIS DEVELOPMENT IN THE MOUSE: EMPHASIS ON THE MACROPHAGE SPHINGOSINE-1-PHOSPHATE RECEPTOR 1 - Gonzalez Jara, Leticia A (My University, 2016)
Atherosclerosis is a chronic inflammatory disease affecting large- and medium-sized arteries and is considered the major cause behind cardiovascular diseases (CVD). Elevated low-density lipoprotein (LDL)-cholesterol and low high-density lipoprotein (HDL)-cholesterol are considered major risk factors for the CVD. HDL mediates a variety of atheroprotective actions, many of them involving the interaction with the scavenger receptor class B, type 1 (SR-B1). Despite the efforts placed in raising HDL-cholesterol, no improvement has been achieved in reducing CVD risk, suggesting that other components of the HDL particles may be responsible for HDL-mediated atheroprotection. One of these may be sphingosine-1-phospate (S1P). In this thesis, the role of S1P receptors (S1PRs) in atherosclerosis is explored, with emphasis in macrophage apoptosis. In particular, the importance of the macrophage S1PR1 and its role in apoptosis and atherosclerosis was evaluated. We demonstrated that diabetes exacerbates atherosclerosis development and myocardial infarction in SR-B1 KO/apoE-hypomorphic mice and that treatment with FTY720, a S1PR agonist, protects against diabetes pro-atherogenic effects. We also show that S1PR1 agonists protected macrophages against apoptosis through phosphoinositide 3-kinase (PI3K)/AKT, and that HDL failed to protect S1PR1 deficient macrophages against apoptosis. In vivo, macrophage S1PR1 deficiency translated into increased atherosclerosis, necrotic core formation and numbers of apoptotic cells in the atherosclerotic plaque. BIM deficiency in BM cells was protective against atherosclerosis development and HDL treatment reduced BIM protein levels in cells exposed to ER stressors, suggesting that the pro-apoptotic protein may be an important target for HDL in macrophages. We conclude that signaling through the S1PRs, in particular S1PR1 is important in controlling macrophage apoptosis and atherosclerosis development. Our data suggests that S1PR1 signaling axis and the pro-apoptotic protein BIM play an important role in mediating HDL anti-apoptotic signaling, however further studies are required to clarify the interaction between all of these factors.
MOLECULAR MECHANISMS OF ATHEROSCLEROSIS IN THE MOUSE
Keywords: atherosclerosis; macrophage apoptosis; sphingosine-1-phosphate receptors; high density lipoprotein